Nasal irrigation using saline at room temperature or body temperature: which is more beneficial in chronic rhinosinusitis? - Behera, Subrat K.; Radhakrishnan, Sruthi Thattamparambil; Swain, Smruti (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Mucociliary clearance in nasal mucosa shows changes with temperature. In cold climate, it is expected to decrease, thus contributing to exacerbation of rhinosinusitis symptoms. If we raise the temperature of saline used for nasal irrigation to the normal body temperature, can it overcome this problem in cold climate? This study aims to examine whether irrigation using saline that is heated to 37°C has any superiority compared to irrigation using saline at 180C in rhino sinusitis treatment. Methods: Prospective double blind study done in a tertiary care centre from November 2017 to March 2018. 32 patients of chronic rhinosinusitis were divided into 2 groups. Group A received saline nasal irrigation using saline at 18oc and Group B received irrigation with saline at 37oc for 2 weeks. Saccharine transit time and sino nasal outcome test (SNOT-22) scores were calculated before and after treatment in both groups and the results compared. Results: Saccharine transit time improved from mean pretreatment value of 12.4±5.52 minutes to 9.1±6.3 minutes in Group A and from 12.82±6.3 to 8.5±6.45 in Group B (p=0.0212). Mean SNOT-22 score decreased from 58.8±5.6 to 41.4±4.8 in Group A and from 57.5±4.2 to 37.9±5.1 in Group B after treatment (p<0.05). Conclusions: Nasal irrigation using saline at 370C is more effective than saline at 18°C in increasing mucociliary clearance and improving symptoms in chronic rhinosinusitis patients.